Badan Perwakilan Desa: Harapan Bagi Pembaharuan Desa - Prihatin, S. Djuni; Suyatna, Hempri (Jurnal Ilmu Sosial dan Ilmu Politik, 2001)
A stepforward in institutiorzalising democratic governance at the grass-roots level has been marked with the establishment of village representative body (Badan Perwakilan Desa, known as BPD). This article spells out various expectation embedded within such initiatives and assesses how the BPD lead to a more comprehensizie political reform at a grass roots level in Indonesia.